The Relationship between Cognitive Function and Social Interaction in the Elderly at the Tresna Werdha Bondowoso Social Services Technical Implementation Unit - Novita Elisa; Sofia Rhosma Dewi; Yeni Suryaningsih (Penerbit Hellow Pustaka, 2025)
Background: Elderly individuals are at the final stage of human life, experiencing gradual physical, mental and social decline. One of the common problems among the elderly is cognitive impairment and poor social interaction. Research Objectives: This research aims to determine the relationship between cognitive function and social interaction abilities in the elderly at the Tresna Werdha Bondowoso Social Services Technical Implementation Unit. The aim of this research is to analyze the extent to which cognitive function influences social interaction abilities in the elderly. Research Method: This research used a cross-sectional design with a sample of 74 respondents selected through simple random sampling. The instruments used include the Mini-Mental State Examination (MMSE) to measure cognitive function and a social interaction questionnaire. Research Results: The results show that there is a strong relationship between cognitive function and social interaction abilities in the elderly, with a correlation degree of 52.8%. The results of this study found that cognitive function in social interaction was 96.7%. Based on the research results obtained according to the sperman rho statistical test, it was found that the p value was 0.001 < 0.966 so that H1 was accepted which shows that there is a relationship between cognitive function and social interaction in the elderly with a value of r = 0.966 so that the level of strength of correlation between cognitive function and social interaction has a very strong correlation value with a value of 0.000. Conclusion: Cognitive function has a significant influence on social interaction abilities in the elderly. Elderly individuals with good cognitive function tend to have better social interaction skills